English for Specific Purposes Teachers’ Perceptions of Interdisciplinary Collaboration in Writing Classes - Tiongson, Marella Therese A. (Journal of English Studies and Comparative Literature, 2019)
Interdisciplinary collaboration between language teachers and content specialists is an important activity in English for Specific Purposes (ES P). However, collaboration is an under-researched practice in the Philippines, where some ES P teachers have difficulties in teaching specialized writing courses due to lack of training in technical content. Thus, exploring collaboration is worthwhile, especially because of its potential in informing curricular decisions in specialized writing classes as a result of curricular revisions in the K to 12 program. This exploratory qualitative study reports on the perspective of two ESP teachers, who are involved in teaching English for the Professions, on interdisciplinary collaboration. Data were collected through semi-structured interviews, and the informants’ responses were thematically coded to reveal how they understand collaboration, what its benefits and challenges are, and how it can be established. This study has implications for understanding how interdisciplinary collaboration may work and be sustained in the Philippine university context.